SCIENTIFIC ARTICLE WRITING TRAINING PROGRAM FOR PROSPECTIVE ELEMENTARY SCHOOL TEACHERS - Yosi Gumala; Husna Farhana (Yayasan Education and Social Center, 2021)
Because of the numerous issues that arise in the language learning process in the classroom and the lack of interest among prospective teachers in conducting classroom action research, this task is complete. And, the teacher still does not understand the concept and is skilled at writing good scientific articles. This activity aims to provide understanding to teachers, make teachers proficient in writing proposals, and increase the motivation of teachers to conduct classroom action research. The location of the activity is Bhayangkara University, Greater Jakarta. The number of participants is 100 people. The model used is mentoring or counseling on basic concepts and training in proposal writing and analyzed with a qualitative descriptive approach. The activity method is a presentation in which prospective elementary school teachers compile scientific articles and present them to the other participants. The observations showed positive things. Namely, the teachers were enthusiastic in participating in the activities and their desire to practice them in learning activities. In addition, participants can produce sample proposals. The participants are looking forward to follow-up activities